(untitled) (Damascus University Journal for legal sciences, 2026)
The principle of litigation is one of man’s most important natural rights, through which every individual can repel any aggression that constitutes aviolation of his rights and freedoms. Therefore, modern constitutions stipulate this right as one of the necessary guarantees to strengthen the principle of the rule of law on the one hand and protect the rights and freedoms of individuals on the other hand. However, ordinary legislation in some countries came and took advantage of this right under different justifications and grounds, as is the case for the theory of works of sovereignty. In this study, we will discuss the concept of the right to litigation and the position of the constitutional and ordinary legislature on this right in Syria and compare it with what is the case in France and Egypt. This study also tackles the theory of sovereignty acts through analytical study for the theory’s concept and Criteria for distinguishing it, we will also shed the light to, the position of the normal or constitutional legislative. Through this study, we will review the position of jurisprudence on theory of sovereignty in France, Egypt, and Syria.